The Interrelation of Sundanese Culture in the Development of Children's Books in the Betawi’s Culture Elementary Schools - Sani Aryanto; Panisa Marliana; Bunga Aulianesia; Anna Zalfah Nurullail; Ari Wibowo (CV. Creative Tugu Pena, 2024)
his study aims to provide a comprehensive overview of the process of making a Sundanese cultural literacy decodable book, which aims to improve Sundanese cultural literacy in students who are included in the category of early readers in elementary school. The study involved 90 students in grades four to six in elementary school, who were included in the early reader category. This research resulted in a book that is considered to have internalized Sundanese cultural values in the scope of elementary school education which was tested to two early literacy experts by producing an average score of 88.1% in the Very Feasible category and obtained evaluation results with a score of 80.75% in the feasible category from students and 87.5% in the Very feasible category from teachers. Therefore, this research is expected to contribute to increasing the quantity and quality of decodable book that contain Sundanese cultural values.